PERAN INOKULUM Rhizobium TERHADAP PERTUMBUHAN DAN PRODUKSI KEDELAI DI TANAH MASAM DALAM RUMAH KACA - , DYAH PARMAWATI, Prof. Dr. Ir. Erni Martani ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Soybean is one of an important agricultural comodities in Indonesia and its production is still very low. Increasing the soybean production can be achieved by extensification measures to out side of Java, i.g. Sumatera and Borneo island, eventhough they has constraints on their acidity of soils, which can give the negative impact to the growth of nitrogen fixation bacteria and its soybean production. The purpose of research is to observe the role of Rhizobium inoculum acid tolerant (INORHIZO) on the growth and production of soybean plant in acid soil. The research was conducted in the glass hause, polybag scale, using mineral soil and Rhizobium inoculum (LEGIN) as a comparison model, and also CRD was done. Results showed that INORHIZO and some of liming doses treatments can increase the growth and production of soybean better than others, i.g. LEGIN inoculum, that are 0,52 ton/ha and 0,32 ton/ha respectively. The better result of liming dose is 10 g/kg of soil and nitrogen fixation up to 0,497 mmol/g.